Mechanical licensing of the NLRP3 inflammasome in hypertensive vasculature: Integrin mechanotransduction and cytoskeletal control of vascular inflammation - Noof Abdulrahman Alrabiah; Safwan Abid Al-hameed Suliman; Lashin S. Ali; Waseem Ali Hasan; Amany Said Sallam; Rabab S. Hamad; Etedal Ahmed A. Ibrahim; Eman Hamza; Nesreen Elsayed Morsy; Ahmed Shata; Hanan Eissa; Alshaimaa A. Farrag; et al. (Tissue and Cell, 2027)

Dysregulation of circ-SMARCA5, circ-RHOT1, and HNF1A and the association of HNF1A polymorphisms with hepatocellular carcinoma - Basma A. Ibrahim; Basma S. Elsayed; Mohamed Abdelaziz Gendia; Manar Moustafa; Ansam M. Z. El Desoky (Molecular Biology Reports, 2026)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Pharmaceutical Innovation in Salivary Biomarker Research: Transforming Oral Healthcare through Nanotechnology and Point-of-Care Systems: A Narrative Review - Akram N. Salah; Ahmed E. Elesawy; Mohamed Bakr Zaki; Ahmed I. Abulsoud; Gharieb S. El-Sayyad; Wagiha S. Elkalla; Nehal I. Rizk; Osama A. Mohammed; Hend H. Mohamed; Nourhan H. Elshami; Asmaa A. Ibrahim; Salma W. Elsayed; et al. (Journal of Pharmaceutical Innovation, 2026)

Enhanced mitigation of diabetic myocardial injury in rats via modulating the adiponectin/IRS-1/PI3K/p-AKT/FOXO-1 signaling by combining methotrexate and insulin - Mohamed S. Elsayed; Mahmoud Elshal; Manar G. Helal; Tarek Ibrahim (Molecular Biology Reports, 2026)

Dietary lemon essential oil mitigates metalaxyl-induced oxidative stress, hematological disruptions, and immunotoxicity in Nile tilapia (Oreochromis niloticus) with associated changes in splenic MAPK-and caspase-related gene expression - Elsayed M. Younis; Afaf N. Abdel Rahman; Tarek Khamis; Abdelwahab A. Abdelwarith; Simon J. Davies; Faozi S. Shamlol; Nehal A. Younis; Rowida E. Ibrahim; Gehad E. Elshopakey (Research in Veterinary Science, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Influence of Infiltration Methods on Runoff Estimation for Sustainable Rainwater Harvesting in Arid Regions - Ismail Abd‐Elaty; Alban Kuriqi; Elsayed M. Ramadan; Marmar Mabrouk; Ibrahim Elbagory (Irrigation and Drainage, 2026)
Arid regions face severe water stress due to limited rainfall and growing water demand, making accurate runoff estimation essential for sustainable water management. Infiltration processes strongly influence both hydrograph volume and peak discharge, and their accurate estimation is critical for hydrological modelling. This study applies the Watershed Modelling System (WMS) to evaluate rainwater harvesting potential in the Wadi El‐Aawag watershed, southwestern Sinai, Egypt, using four infiltration loss estimation methods: Uniform Loss (LU), Green–Ampt (LGA), Holtan (LH) and the Soil Conservation Service (SCS) curve number method. Each method accounts for soil type, land cover and infiltration characteristics, enabling assessment across recurrence intervals of 5, 10, 25, 50 and 100 years. The results indicate considerable variation in runoff response across the selected methods. The estimated runoff volumes were 35.11, 24.10, 31.65 and 23.57 million m 3 for LU, LGA, LH and SCS, respectively, for recurrence intervals of 100 years. Among the tested approaches, the SCS method provided the most reliable and realistic estimates for the study area. These findings emphasise the importance of method selection when modelling infiltration losses and highlight the role of robust hydrological assessment in optimising rainwater harvesting, mitigating drought risks and enhancing long‐term water security in arid regions.

Adenosine A₂A receptor as a dual-acting molecular switch: Glial morphological changes and neurovascular tissue remodeling in neuroinflammation and neurodegeneration - Heba Ibrahim Abd El-Moaty; Ahmed Sameh; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Norah Suliman Alsoqih; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; et al. (Tissue and Cell, 2026)

Taurine protects against gentamicin-induced neurotoxicity through dual modulation of Nrf2 and NF-κB pathways - Amira E. Farage; Medhat Taha; Basma Adel Khattab; Nawal E. Al-Hazmi; Alaa Eldin Ahmed Mohamed; Marwa M. Mona; Marwa M. Abd-Elsalam; Ahmed Elsayed Elsukary; Mohamed A.F.E. Sarhan; Ahmed shaban Abdelmonsef; Tourki A.S. Baokbah; Ibrahim El-Shenbaby; et al. (Tissue and Cell, 2026)

FOXO3a-mediated structural and cellular remodeling in liver tissue: Implications for apoptosis and homeostasis - Heba Ibrahim Abd El-Moaty; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Simona Cavalu; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Waseem Ali Hasan; et al. (Tissue and Cell, 2026)

Molecularly diverse lonazolac-inspired pyrazole-cyanopyridin-2-one conjugates: design, synthesis, in vitro, in vivo and in silico studies as multi-target anti-inflammatory agents - Marwa A. Aziz; Azizah M. Malebari; Tarek S. Ibrahim; Mohamed F. Radwan; Deiaa E. Elsayed Abouzed; Rasha M. Allam; Majed Alharbi; Ahdab N. Khayyat; Gamal El-Din A. Abuo-Rahma; Mamdouh F. A. Mohamed (Molecular Diversity, 2026)

A new cadinane-type sesquiterpenoid glucoside from Centaurea alexandrina - Ibrahim A. Saleh; Wael M. Elsayed; Taha A. Hussien; Abdelsamed I. Elshamy; Tarik A. Mohamed; Mohamed-Elamir F. Hegazy (Natural Product Research, 2026)

Trientine ameliorates bleomycin-induced pulmonary fibrosis in rats through copper chelation and modulation of the CTR1/LOX/COL pathway - Ibrahim T. Khalil; Mahmoud Elshal; Norhan M. Elsayed; Asmaa Radwan (Inflammopharmacology, 2026)
Pulmonary fibrosis (PF) remains a devastating disease. Copper (Cu), an essential trace element, has been implicated in fibrotic processes in various organs, including the lungs. This study investigated the potential protective effects of trientine (TRI), a copper chelator, against bleomycin (BLM)-induced PF in rats and explored the underlying mechanisms. PF was induced by intratracheal administration of BLM (5 mg/kg). Rats were randomly allocated into seven groups: normal control, TRI alone, BLM control, and four BLM plus TRI prophylactic or therapeutic groups receiving low (55 mg/kg) or high (110 mg/kg) TRI doses orally. Results demonstrated that TRI dramatically reversed BLM-elevated serum levels of lactate dehydrogenase and alkaline phosphatase, markers of tissue damage. The protective effects of TRI were multifaceted: it exhibited potent antifibrotic activity by reducing collagen buildup and inhibiting TGF-β, CTR1, LOX, and COL1 expression; it acted as an antioxidant by increasing antioxidant status and significantly upregulating Nrf2; and it served as an anti-inflammatory agent by decreasing inflammatory cytokines (TNF-α and IL-6) and modulating the NF-κB pathway by increasing NF-κB expression while limiting its activation and nuclear translocation, thereby reducing inflammatory signaling. Histopathological and immunohistochemical analyses confirmed substantial attenuation of collagen deposition and structural lung damage. Overall, TRI demonstrated potent antifibrotic, antioxidant, and anti-inflammatory properties, effectively protecting lung tissue against BLM-induced injury. These findings highlight copper chelation as a promising therapeutic strategy for pulmonary fibrosis and warrant further investigation into TRI’s clinical potential.

Investigation of the Antibacterial Effectiveness of Hybrid Recombinant Bacteriocins Circular Enterocin and Pyocin L1 Derived from Pseudomonas aeruginosa and Enterococcus faecalis - Lina Jamil Abdel-Hafez; Mohamed Salah Basiouny; Islam Yousif Mostafa; Rehab Moustafa; Khaled Abuelhaded; Haytham Mohamed Abd-Elhalim; Abanoub A. S. Shaker; Hassan Elsayed; Olfat Salem; Amir Mahfouz Mokhtar Sarguos; Ahmed Hassan Ibrahim Faraag (Biochemical Genetics, 2026)

Sustainable management of olive trees under saline irrigation and soil conditions using micro-irrigation systems and remote sensing - Mohamed M. Mahmoud; Mohamed E. Abuarab; Ayman Shaban; Ibrahim Hmmam; Asmaa Gamal Abd El-hamied; Amr Mossad; Ali Mokhtar; Elsayed Youssief Ghoniem (Irrigation Science, 2026)
The study was carried out to examine the sustainable management of irrigation water for olive cultivation in sandy soils with varying levels of water salinity at a farm situated in the Regwa region of EL-Beheira Governorate, Egypt, which is noted for its arid climate, aiming to improve the effective utilization of sustainable ecosystems while optimizing economic returns for agricultural producers. Field experiments were implemented over two successive growing seasons, specifically 2022–2023 and 2023–2024, employing seven distinct irrigation methodologies: micro-sprinklers, T-tape GR drippers, Root Zone Watering System (RZWS), inline drippers, inline PC drippers, mist sprayers, and bubblers. In the 2022–2023 season, the inline dripper treatment yielded the highest output of 13.78 ton ha −1 , followed by the inline PC dripper and micro-sprinkler systems, which yielded 13.20 ton ha −1 and 12.45 ton ha −1 , respectively. In contrast, the mist sprayer treatment produced the lowest yield at 7.61 ton ha −1 . The oil content in olive fruits reached optimal levels under bubbler and inline PC dripper treatments in the second growing season at 40.0% and 39.87%, respectively. Conversely, the minimum oil content was recorded under micro-sprinkler and inline dripper treatments in the first growing season, yielding 34.31% and 34.36%, respectively. During the first growing season, the inline dripper exhibited irrigation water productivities (IWPs) of 31.60 kg m −3 , followed by the inline PC dripper with an IWP of 30.28 kg m −3 . In stark contrast, the mist sprayer reported the lowest IWPs of 0.74 kg m −3 in the second growing season. The distribution patterns of soil moisture and salinity within the root zone were analyzed utilizing Surfer software. The most significant net farm income (NFI) was attained under the inline PC dripper treatment, with an NFI of 38,664.35 US$ y −1 , succeeded by the inline dripper and micro-sprinkler treatments with NFIs of 36,010.95 and 30,265.94 US$ y −1 , respectively; the mist sprayer demonstrated the lowest NFI at 17,186.49 US$ y −1 .

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Uterine and ovarian hemodynamics assessment of Camelus dromedarius with hormonal alterations and anatomical and histological architecture - Elshymaa A. Abdelnaby; Asmaa M. Ibrahium; Aya M. Mekkawy; Ibrahim A. Emam; Alaa H. Elsayed (Veterinary Research Communications, 2026)

Sustainable Africa space governance: Strategic decision support framework, opportunities, challenges and solutions - Rania Elsayed Ibrahim; Alaaeldin S. Hassan; Tshiamo Motshegwa (Journal of Space Safety Engineering, 2025)

Exploring the Efficacy and Safety of Argatroban as an Adjunct to Antiplatelet Therapy in Ischemic Stroke Patients: A Systematic Review and Meta-analysis - Yousr Ahmed; Mostafa Hossam El Din Moawad; Gulnaz Bahtiyarova; Younes Nabgouri; Mohammed Elkholy; Reham M. Wagih; Ibrahim Serag; Ibraheem M. Alkhawaldeh; Mohamed Abouzid; Mahmoud Elsayed (Translational Stroke Research, 2025)

Correction: Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Assessment of mechanical properties and environmental impacts of eco-friendly lightweight geopolymer concrete using popcorn aggregates from recycled plastic waste - Omar Mohamed Omar Ibrahim; Nour Bassim Frahat; Hossam Hemdan El-Fahhar; Saber Elsayed Saber; Sally Hosny (Innovative Infrastructure Solutions, 2025)
The increasing challenges in natural resource consumption and cement production have intensified interest in recycling and sustainable construction materials. In this study, an environmentally friendly lightweight geopolymer concrete (LWGPC) was developed by integrating two recycled components: fly ash (FA) as the primary binder and a novel lightweight coarse plastic aggregate (LCPA), produced from locally recycled plastic waste and commonly referred to as “popcorn aggregates”, which was used to fully replace natural coarse aggregates. Fourteen mixes were prepared with varying sand-to-LCPA ratios, while maintaining constant fly ash content and a fixed alkaline activator. Fresh, physical, and mechanical tests, as well as SEM and EDX analyses, were conducted alongside environmental and economic assessments after curing for 7 and 28 days under direct sunlight. The experimental results revealed that workability improved with increasing LCPA content, with the 1S:2LCPA mix achieving a 54% increase in slump. Dry density decreased gradually, with the 1S:1LCPA mix achieving a 23.1% weight reduction while maintaining structural integrity. Although compressive strength decreased with higher LCPA content, the 1S:1LCPA mix demonstrated a favorable balance between density reduction and strength, recording 30.6 MPa at 28 days. Moreover, the 1S:1.5LCPA mix improved tensile and flexural performance up to the optimal ratio, beyond which reductions occurred. Importantly, these mixes reduced energy consumption by 41.09%, CO 2 emissions by 40.52%, and overall cost by 31.58% compared to the control. The results highlight the potential of LCPA as an innovative aggregate, enabling sustainable, cost-effective, and lightweight geopolymer concrete production, with promising applications in non-structural blocks, partition walls, and energy-efficient lightweight panels. Graphical abstract

Impact of Effective Probiotic Microorganisms (EPMs) on Growth Performance, Hematobiochemical Panel, Immuno-Antioxidant Status, and Gut Cultivable Microbiota in Striped Catfish (Pangasianodon hypophthalmus) - Mahmoud Abdullah Elnakeeb; Ahmed Mohamed Ashry; Ahmed Mohamed El-Zayat; Abdel Wahab Abdel-Moez Abdel-Warith; Mahmoud Mohamed Habiba; Elsayed Mohamed Ibrahim Younis; Simon John Davies; Ibrahim Mohamed Ibrahim; Fatma Elzhraa; Ahmed Mohammed El-Sebaey (Fishes, 2025)
Striped catfish, Pangasianodon hypophthalmus, has recently emerged as a promising candidate for Egyptian aquaculture owing to its rapid growth; however, under intensive culture, it is vulnerable to Aeromonas hydrophila. The efficacy of dietary supplementation with effective probiotic microorganisms (EPMs) in enhancing growth performance, feed utilization, physiological health, and disease resistance of P. hypophthalmus against A. hydrophila challenge was evaluated. A 90-day feeding trial was conducted with 300 fish randomly distributed into four triplicate groups (25 fish per replicate) reared in 12 indoor fiberglass tanks: a control and three groups receiving EPMs at inclusion levels of 1.5%, 3%, and 4.5%. The results showed significant, dose-dependent improvements across all EPMs-supplemented groups in survival, growth rates, feed utilization, and hematological parameters (RBC, Hb, PCV, WBC, and lymphocytes). Dietary EPMs led to significant improvements (p ≤ 0.001) in digestive efficiency, protein and lipid metabolism, antioxidant enzyme activity, immune performance, and the ability of striped catfish to withstand A. hydrophila infection. Hepatobiliary enzyme activities (ALT, AST, and ALKP), glucose levels, lipid profile markers, and hepatic MDA exhibited a significant linear decrease (p ≤ 0.0001) with increasing EPMs levels. The gut microbial composition showed a dose-dependent increase in beneficial lactic acid bacteria (LAB) and a reduction in TAPC, pathogenic coliforms (TFCC), and Vibrio spp. (TVC). These results demonstrate the dose-dependent effects of EPMs on enhancing aquafeed efficiency, overall health, and innate immunity in striped catfish.

Energy-saving potential in buildings by cement bricks made with date seed aggregates and Arundo donax fiber with thermal and mechanical assessment - Mohamed Ibrahim Abdelhady; Mostafa Amin Elsayed; Asmaa Abd Elmoneim Fahmi; Nour Bassim Frahat (Energy and Buildings, 2025)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

Bioprotective potential of biosynthesized copper oxide nanoparticles and copper phosphite against Alternaria-solani-induced leaf spot in pepper plants - Mohamed S. Attia; Mohamed H. Moustafa; Amr H. Hashem; Salah M. Elsayed; Abeer S. Aloufi; Ismail Mostafa Ismail Abdelaleem; Karim A. Alshahed; Abdelrhman S. Ismail; Abdelrhman M. Ibrahim; Mostafa A. Abdel-Maksoud; Abdulaziz Alamri; Hossam Ebaid; et al. (Antonie van Leeuwenhoek, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

Assessment of the efficacy of seven plant extracts to inhibit strawberry bacterial leaf blight disease caused by Pantoea ananatis - Maurice Sabry Mikhail; Hamdy Ibrahim Seif El-Nasr; Elsayed Embaby; Tarek Gomaa Abdel-Gaied; Maryan MakramYoussef (European Journal of Plant Pathology, 2025)
This study investigates the antibacterial activity of the plant extracts in order to develop strategies for the prevention and management of Pantoea ananatis in strawberry. Seven plant extracts including eucalyptus, fenugreek, garlic, lantana, moringa, onion and pomegranate fruit peels were usedat concentrations of 40, 60, 80 and 100 mg/ml to test their efficacy against Pantoea ananatis in in vitro tests. The eucalyptus and pomegranate fruit peel treatments did not show inhibition of the growth of the pathogen. The garlic extract showed the strongest antibacterial activity against Pantoea ananatis , followed by lantana. Under field conditions, the effect of the ethanol extracts from garlic and lantana, applied by root dipping and foliar spraying were assessed. The antibacterial effect was larger when sprayed on the foliage. Disease severity was reduced by 56.0%. The results show that the vegetative growth and fruit quality of strawberry plants were significantly improved after foliar sprays. After foliar sprays with the garlic extract, the activities of several defense-related enzymes were significantly enhanced, including peroxidase, polyphenol oxidase, and β-1,3-glucanase. In this study, phenolic acids were identified in both garlic and Lantana ethanol extract, which could act as an active inhibitor of bcteria.

Tailored ion-imprinted polymer for europium(III) recovery: A cellulose-based click chemistry approach - Nadia H. Elsayed; Duna A.K. Alenazi; Kholoud M. Alnahdi; Shareefa Ahmed Alshareef; Menier Al-Anazi; Nawaa Ali H. Alshammari; Maha Ali Aljowni; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Jawza Sh. Alnawmasi; Yasmeen G. Abou El-Reash; M. Monier; et al. (Journal of Water Process Engineering, 2025)

Host-Parasite interactions in the Arabian Gulf: a morphological and molecular study of Cymothoa pulchrum in Parastromateus niger - Afaf Abdullah Mubark Al-Salem; Hanadi B. Baghdadi; Mustafa M. Ibrahim; Abdelgayed M. Younes; Elsayed M. Bayoumy (Zoomorphology, 2025)

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Dietary intervention of ginger and black seed oils boosted hematology, biochemical profile, and antioxidant-immune responses in Oreochromis niloticus challenged with Aeromonas veronii - Shaimaa E. Ibrahim; Fatma M. Abdelhamid; Elsayed Nabeeh Abou ElGheit; Mohamed A.H. El-kady; Gehad E. Elshopakey; Engy F. Risha (Aquaculture, 2025)

Behavioral and neurological responses of Oreochromis niloticus to chronic cyclic hypoxia: mechanistic insights into hypoxia-responsive genes, pro-inflammatory and apoptotic pathways: role of camel whey protein hydrolysate - Amany Abdel-Rahman Mohamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Rowida E. Ibrahim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Abd Elhakeem El-Murr; Simon J. Davies; Yasmina M. Abd-Elhakim (Veterinary Research Communications, 2025)

Mitigating potential of Malva parviflora leaves against Polyram DF (dry flowable) toxicity in Nile tilapia: immune/apoptotic markers, biochemical, antioxidant, and histopathological insights - Elsayed M. Younis; Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Engy Mohamed Mohamed Yassin; Kholoud A. Alhallag; Mohammed S. Sobh; Mohamed Shaalan; Tarek Khamis; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Investigating the impact of camel whey protein hydrolysate on cyp1a1 and keap1/nrf2 expression in hypoxic stress-affected liver tissue of Oreochromis niloticus - Amany Abdel-Rahman Mohamed; Afaf A. Kishta; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Yasmina M. Abd-Elhakim; Rowida E. Ibrahim; Mohamed M. M. Metwally; Tarek Khamis; Ali Osman; Simon J. Davies; Mohamed A. Elbealy (Journal of Comparative Physiology B, 2025)

Limettin and PD98059 Mitigated Alzheimer’s Disease Like Pathology Induced by Streptozotocin in Mouse Model: Role of p-ERK1/2/p-GSK-3β/p-CREB/BDNF Pathway - Rofida M. Hassan; Nesrine S. Elsayed; Naglaa Assaf; Barbara Budzyńska; Krystyna Skalicka-Wożniak; Sherehan M. Ibrahim (Journal of Neuroimmune Pharmacology, 2025)
Sporadic Alzheimer’s disease (SAD) represents one of the major memory deficits that is characterized by tau hyperphosphorylation and amyloid beta (Aβ) deposition in the brain. Both are considered AD hallmarks which are mediated through neuroinflammation, oxidative stress, and cholinergic circuit interruption. This study aimed to show how limettin and PD98059 exert a neuroprotective effect against SAD and the possible role of the extracellular regulated kinase ( p- ERK1/2) and glycogen synthase kinase-3 beta ( p- GSK-3β) (Ser9)/cAMP-response element binding protein ( p- CREB) (Ser133)/brain derived neurotrophic factor (BDNF) pathway. Control animals (Group I) received the vehicles, group II received PD98059 (10 mg/kg/i.p), while group III was administered limettin (15 mg/kg/i.p). Additionally, the other three groups received a single dose of streptozotocin (STZ; 3 mg/kg/ICV), where group IV served as the SAD group, while groups V and VI received PD98059 and limettin daily for 3 weeks, respectively. The SAD animals receiving PD98059 and limettin increased the number of arm entries, % alternations in Y-maze, with reduction in mean escape latency, increase in time spent in target quadrant and platform crossing in Morris Water Maze, compared to the SAD group. Additionally, PD98059 and limettin administration to the STZ group downregulated persistent activation of p -ERK1/2 which in turn increased p -GSK-3β (Ser9), leading to enhanced p- CREB (Ser133) and BDNF expressions, as well as reducing inflammatory markers viz ., nuclear factor-kappa B and interleukin-6, leading to decreased Aβ deposition. Both treatments reduced immunohistochemical p -tau expression, brain edema, and increased intact neuron cells remarkably. Thus, based on these findings, PD98059 and limettin may have promising effects in protecting against SAD. Using blockers/inhibitory molecules are recommended to confirm effect through the corresponding pathway.

The potential of bone marrow derived mesenchymal stem cells in treating cisplatin induced sensorineural hearing loss in a guinea pig animal model - Mohamed Hassan Ali Elsayed Abdelwahed; Mohamed Hussien Badreldin; Ibrahim Hassan Ibrahim; Reham Farouk Zittoon; Rania A. Galhom; Sally S. Mohammed; Yehia Mohamed Ashry (Tissue and Cell, 2025)

Alleviative potential of dietary essential oils against nickel toxicity triggers neurobehavioral abnormalities, biochemical dysfunction, and histopathological alterations in Nile tilapia - Shaimaa A. A. Ahmed; Ali Adel Ali Ahmed; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Mai Farag Saad; Simon J. Davies; Rowida E. Ibrahim; Asmaa Edrees (Veterinary Research Communications, 2025)

Ameliorative potential of Populus alba leaf powder against hexaflumuron exposure in Nile tilapia: immune-antioxidant, biochemical, histological, and transcriptomic analysis - Rowida E. Ibrahim; Mohamed F. M. Farag; Mohammed S. Sobh; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Shefaa M. Bazeed; Aya Elgamal; Tarek Khamis; Simon J. Davies; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Carbonate alkalinity induces stress responses and renal and metabolic disorders in Nile tilapia: mitigation by camel whey protein hydrolysate diet - Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Amany Abdel-Rahman Mohamed; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Yasmina M. Abd-Elhakim (Fish Physiology and Biochemistry, 2025)

Adaptation and development plans of the Egyptian ports under the impacts of climate change - Ahmed A. Romya; Ahmed Elsayed Elkut; Asmaa A. Abu Zed; Hossam M. Moghazy; Maysara Khairy El-Tahhan; Akram Soliman; Mona G. Ibrahim; Moheb Iskander; Mahmoud Sharaan (Ocean & Coastal Management, 2025)

Enhancing the performance of rigid pavement slabs using sugarcane bagasse ash and macro synthetic fibers - Esraa Elsayed Elayouty; Shady Rezk Ragheb; Ahmed Mohammed Youssef; Marwa El-Sayed El-Bany; Ibrahim Saad Agwa (Innovative Infrastructure Solutions, 2025)
This study uses a few materials with various ratios, such as sugarcane bagasse ash (SBA) and macro synthetic fiber (MSF), to enhance the rigid pavement slab (RPS) load-carrying capacity (LCC). In the study presented herein, the investigation was developed in two phases. Firstly, we selected materials and evaluated their physical, mechanical, and chemical characteristics. Nine different concrete mixes were designed as part of the study. The investigation focused on the ratio of replacement SBA used, which ranged from 0 to 25% by weight of the cement content, and MSF ratios 0.5%, 1%, and 1.5% by volume of concrete mixture. Compressive strength (CS), flexural strength (FS), slump, and splitting tensile strength (STS) were used to assess each mixture’s characteristics. SEM was also used to illustrate the specifics of the SBA results. Accordingly, three mixes have been chosen to be used in the next. In the second phase, a study was conducted on the ultimate LCC for RPS internal, edge, and corner. Nine RPS measuring 800 mm × 800 mm × 50 mm were constructed and subjected to a static load at three different locations. The optimal ratios for high mechanical properties are 10% SBA replacement for cement content and 1% MSF inclusion by volume in the concrete mixture. The CS of SBA10 increases by approximately 7.32% compared to its reference mixture. With the SBA10F1 mix design, there is a 34% increase in ultimate LCC for internal loading, a 33% increase for edge loading, and a 36% increase for corner loading compared to its reference mixture. This research presents new insights into the combined use of SBA and MSF, contributing to the development of more sustainable RPS.

Dietary Prunus armeniaca augments antioxidant-immune-capacity, absorptive function, and growth and upregulates nutrient transporters and immune-regulatory genes of Oreochromis niloticus - Afaf N. Abdel Rahman; Sara T. Elazab; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2025)

Potential Impact of SOD2 (rs4880; p.Val16Ala) Variant with the Susceptibility for Childhood Bronchial Asthma - Nahla H. Anber; Hanaa Elsayed Ahmed Shahin; Heba K. Badawy; Enas A. Oraby; Sameh A. Mohammed; Esraa Ibrahim A. Shaaban; Zeinab Rizk Attia; Shereen Mohamed; Mona Farag Shabana; Mohamed Adel El‑Eshmawy; Riham Elsayed; Afaf M. Elsaid; et al. (Biochemical Genetics, 2025)

Potential of using kidney bean (Phaseolus vulgaris L) protein hydrolysate as a plant protein supplement in Nile tilapia (Oreochromis niloticus) diets: effects on growth, hematology, histology, and blood biochemical parameters - Shimaa A. Amer; Rowida E. Ibrahim; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Simon J. Davies; Medhat S. Shakweer (Aquaculture International, 2025)

New Ionic Liquid Forms of Antituberculosis Drug Combinations for Optimized Stability and Dissolution - Hanan E. Rasmy; Sara A. Abouelmagd; Elsayed A. Ibrahim (AAPS PharmSciTech, 2025)
Isoniazid (INH) and rifampicin (RIF) are the two main drugs used for the management of tuberculosis. They are often used as a fixed drug combination, but their delivery is challenged by suboptimal solubility and physical instability. This study explores the potential of active pharmaceutical ingredient-ionic liquids (API-ILs) to improve the physicochemical and pharmaceutical properties of INH and RIF. Antitubercular drugs, INH, or RIF, were paired with different counter ions (ascorbic acid (AsA), citric acid (CA), tartaric acid (TA), benzoic acid (BA), salicylic acid (SA), and p-amino salicylic acid (PAS)) using the solvent evaporation method. INH and RIF API-ILs were formed successfully using AsA and CA counter ions. IL formation was examined and analyzed using Fourier transform infrared (FTIR) spectroscopy, x-ray powder diffraction (XRPD), and polarized optical microscopy (POM). XRPD and POM confirmed their amorphous nature, while FTIR analysis demonstrated the contribution of hydrogen bonding to IL formation. IL formation enhanced the storage stability of the INH + RIF mixture in the presence of CA. Moreover, RIF-CA IL significantly increased the rate and extent of RIF dissolution. An effect that is unattainable with the RIF/CA physical mixture. Thus, API-IL formation not only enhances RIF dissolution but also facilitates the preparation of stable, compatible INH-RIF combinations. Graphical Abstract

Retraction notice to “The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological/immunohistochemical investigation of gills” [Aquaculture 584 (2024) 740639] - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Valorization of abattoir water discharge through phycoremediation for enhanced biomass and biodiesel production - Mahdy Elsayed; Yevheniia Mysnyk; Mohamed Mahmoud-Aly; Ehab Mostafa; Adel W. Almutairi; Doaa G. Abbas; Mohamed M. Ibrahim; Dieter Hanelt; Abdelfatah Abomohra (Biomass and Bioenergy, 2024)

Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Camel whey protein hydrolysate diet mitigates alkaline stress–induced biochemical disorders and restores the target of rapamycin, MAPK pathway, and autophagy-related gene expression in Nile tilapia - Rowida E. Ibrahim; Gehad E. Elshopakey; Mohamed Y. M. Aly; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Yasmina M. Abd-Elhakim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Amany Abdel-Rahman Mohamed (Aquaculture International, 2024)

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Efficacy of the dietary Malva parviflora leaves in modulating immune-antioxidant functions, resistance to Candida albicans and Streptococcus agalactiae infection, digestive/absorptive capacity, and growth of Nile tilapia (Oreochromis niloticus) - Afaf N. Abdel Rahman; Yasmin A. Reyad; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Nehal Abd EL-Mageed; Afaf A. Kishta; Asmaa Yaseen; Simon J. Davies; Rowida E. Ibrahim (Aquaculture International, 2024)

Marine Smenospongia extract mitigated co-infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia: insights into promoting growth performance, immune, antioxidant and autophagy defenses, and suppression of endoplasmic reticulum stress-related genes - Doaa Ibrahim; Ioan Pet; Reham G. A. Anter; Abdelwahab A. Abdelwarith; Mona Mohammed I. Abdel Rahman; Basant M. Shafik; Elsayed M. Younis; Asmaa Basiony; Shimaa A. E. Atwa; Aya Sh. Metwally; Heba A. Tolba; Mirela Ahmadi; et al. (Frontiers in Marine Science, 2024)
Identifying novel natural sources from the marine environment with unique immunomodulatory and antioxidant efficacies is of interest in intensive fish farming. In this sense, marine sponge extract derived from Smenospongia (SS-extract) was tested for its potential anti-inflammatory, antioxidant and antimicrobial activities during the concurrent infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia. A total of 625 Nile tilapia fingerlings were distributed into five groups: the control group (with no additives) and four groups fed the control diet fortified with SS-extract at 50, 100, 150, and 200 mg/kg, respectively, for 60 days. The parasitic challenge with Trichodina sp was done at the endpoint of the feeding trial and at 7 days post-infection (dpi); the fish were coinfected with F. columnare . A significant improvement in growth-related parameters of Nile tilapia was detected in the groups that received SS-extract at the levels of 150 and 200 mg/kg. The scavenging ability for free radicals (2,2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH)) was maximized with higher SS-extract supplementation levels. Simultaneously, the antioxidant defense of the Nile tilapia fed 150 and 200 mg/kg was augmented with a decline in oxidation-associated indicators [reactive oxygen species (ROS), hydrogen peroxide (H 2 O 2 ), and malondialdehyde (MDA)]. The higher concentrations of SS-extract in the feed potentiated the immune response of Nile tilapia before infection and even after coinfection and was paralleled by a subsiding in the exaggerated inflammatory response after concurrent infection. Concurrently, the mRNA expression of autophagy-encountered genes ( Atg5 and 12, LC3-II and BCLN1 ) had its highest expression in the fish fed the 200 mg/kg diet with the lowest expression of the mTOR gene in the same fish. The lowest infection intensity and rate and mucus score were displayed in fish fed 200 mg/kg SS-extract at 20 dpi. Interestingly, higher levels of SS-extract triggered antimicrobial peptides (upregulation of Hepcidin and β-defensin-1). In contrast, excessive expression of endoplasmic reticulum genes ( atf4 , JAK1 , PERK , and eif2α ) in the control infected group was downregulated by 200 mg/kg of SS-extract. The quantification of F. columnare indicated that columnaris coinfection severity displayed its lowest rate in the group supplemented with 200 mg/kg of SS-extract. In conclusion, a strategic siting based on fortification of the diet of Nile tilapia with SS-extract was elucidated to reinforce its immune and antioxidant defenses during a concurrent infection.

The role of marine bacteria in modulating the environmental impact of heavy metals, microplastics, and pesticides: a comprehensive review - Islam I. Teiba; Emad H. El-Bilawy; Ibrahim A. Abouelsaad; Akram Ismael Shehata; Mayada Alhoshy; Yusuf Jibril Habib; Nermeen M. Abu-Elala; Nagwa EL-Khateeb; Elsayed B. Belal; Warda A. M. Hussain (Environmental Science and Pollution Research, 2024)

Coupling several spectral manipulations with isosbestic approach to resolve overlapped spectra for concurrent analysis of lamivudine/tenofovir combination: Evaluating environmental sustainability - Bardees Abdelmonem Khashaba; Elsayed A. Ibrahim; Ghada M. Hadad; Michael Gamal Fawzy (Sustainable Chemistry and Pharmacy, 2024)

Hexaflumuron insecticide exposure induces behavior alterations, hemato-biochemical disorders, antioxidant-immune dysfunction, and histopathological alterations in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Basma A. Elshafey; Simon J. Davies; Afaf N. Abdel Rahman (Veterinary Research Communications, 2024)

Rosuvastatin repurposing for prophylaxis against ethanol-induced acute gastric ulceration in rats: a biochemical, histological, and ultrastructural perspective - Hanan I. El-kerdasy; Eman Mohamed Faruk; Dina Allam Abdelmaksoud Hassan; Ola Elsayed Nafea; Fatma Ibrahim; Rania Abubaker Bagabir; Hala Magdy Anwer; Amany M. Allam (Inflammopharmacology, 2024)

The alleviative effect of Bacillus subtilis-supplemented diet against Vibrio cholerae infection in Nile tilapia (Oreochromis niloticus) - Omnia A. Elewasy; Amira S. Elrafie; Neveen A. Rasheed; Sara H. Adli; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Rowida E. Ibrahim (Veterinary Research Communications, 2024)

The therapeutic role of Azadirachta indica leaves ethanolic extract against detrimental effects of Aeromonas veronii infection in Nile tilapia, Oreochromis niloticus - Hesham A. Khalifa; Esraa Sharawy; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Rowida E. Ibrahim; Shimaa A. Amer; Simon J. Davies; Azza M. A. Abo-Elmaaty (Fish Physiology and Biochemistry, 2024)

Use of remote sensing, spatial and geophysical modeling, and real recharging capabilities to identify suitable areas for groundwater exploitation in dry coastal areas - Hossam H. Elewa; Ahmed M. Nosair; Amin Ibrahim; Martina Zelenakova; Katarzyna Pietrucha-Urbanik; Hazem M. Habib; Nermeen A. Abdel Moneam; Rania M. Ragab; Elsayed M. Ramadan (Journal of Environmental Management, 2024)

Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

Potential inhibitory effect of geraniol isolated from lemongrass ( Cymbopogon commutatus Stapf) on tilmicosin-induced oxidative stress in cardiac tissue - Rebai Ben Ammar; Sarah Abdulaziz Alamer; Maged Elsayed Mohamed; Duaa Althumairy; Saeed Y. Al-Ramadan; Manal Alfwuaires; Nancy S. Younis; Thnaian A. Althnaian; Ibrahim R. I. H.; Peramaiyan Rajendran (Natural Product Research, 2024)

Retracted: The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological / immunohistochemical investigation of gills - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2024)

A comparative novel green reversed-phase high-performance liquid chromatography method for simultaneous determination of ivabradine and carvedilol in tablets and human plasma using UV and fluorescence detectors - Ethar A. Rashad; Samar S. Elsayed; Jenny Jeehan M. Nasr; Fawzia A. Ibrahim (Sustainable Chemistry and Pharmacy, 2024)

Retraction Note: Effects of genistein on pentylenetetrazole-induced behavioral and neurochemical deficits in ovariectomized rats - Amr A. Elsayed; Esther T. Menze; Mariane G. Tadros; Bassant M. M. Ibrahim; Nagwa A. Sabri; Amani E. Khalifa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Sustainable valorization of waste glycerol into bioethanol and biodiesel through biocircular approaches: a review - Mahdy Elsayed; Mohamed Eraky; Ahmed I. Osman; Jing Wang; Mohamed Farghali; Ahmed K. Rashwan; Ibrahim H. Yacoub; Dieter Hanelt; Abdelfatah Abomohra (Environmental Chemistry Letters, 2024)
Liquid biofuels like biodiesel and bioethanol are crucial in the transition to low-carbon and high-energy alternatives to fossil fuels. One significant by-product of biodiesel production is glycerol, which accounts for about 10% of the total conversion output. While waste glycerol poses challenges due to its impurities and contaminants, it also holds potential as a metabolic resource for essential cellular components in microorganisms. Crude glycerol production is reviewed, highlighting relevance in current biodiesel technologies and its biochemical composition. To efficiently utilize waste glycerol, co-valorization with low-cost substrates through biocircular platforms using various microorganisms or insects for second and third-generation oxy-biofuels has been explored. Among these, the black soldier fly larvae have demonstrated higher competitiveness for lipid contents (35–43%), making them a promising organism for recycling waste glycerol into biodiesel production, alongside microalgae and oleaginous yeast. The microbial biodiesel productivity from oleaginous yeast is notably higher (3546 kg ha −1 y −1 ) than soybean biodiesel (562 kg ha −1 y −1 ), while microalgal biodiesel productivity surpasses palm biodiesel by more than 25 times. Remarkably, black soldier fly larvae biodiesel productivity was reported to be ~ 1.7 times higher than microalgae and an impressive ~ 43 times higher than palm biodiesel. Despite their potential for biodiesel production, waste glycerol from biodiesel industry still represents a challenge because of high impurities, high viscosity, and limited direct applications in existing processes. To further enhance energy sustainability and address the challenge of waste glycerol, biocircular platforms are discussed for waste glycerol utilization with domestic wastewater sludge, lignocellulosic biomass, and protein-rich wastes. These platforms offer opportunities to create other sustainable agricultural products while minimizing their environmental footprint.

Use of moringa protein hydrolysate as a fishmeal replacer in diet of Oreochromis niloticus: Effects on growth, digestive enzymes, protein transporters and immune status - Shimaa A. Amer; Afaf N. Abdel Rahman; Mohamed ElHady; Ali Osman; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Amr A. Moustafa; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2024)

The anti-bacterial efficacy of zinc oxide nanoparticles synthesized by Nelumbo nucifera leaves against Clostridium perfringes challenge in Oreochromis niloticus - Rowida E. Ibrahim; Moustafa M.S. Fouda; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Gamal A. Salem; Ahmed Asaid Elkady; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture, 2024)

Nelumbo nucifera synthesized selenium nanoparticles modulate the immune-antioxidants, biochemical indices, and pro/anti-inflammatory cytokines pathways in Oreochromis niloticus infected with Aeromonas veronii - Rowida E. Ibrahim; Gehad Elshobaky; Mohamed ElHady; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Suzan K. Murad; Engy Mohamed Mohamed Yassin; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2024)

Novel green HPTLC and organic solvent-free micellar LC methods for the simultaneous determination of Ozenoxacin and benzoic acid; greenness assessment and applications - Adel Ehab Ibrahim; Mohamed Farouk Taher; Alaa El Gindy; Elsayed A. Ibrahim (Sustainable Chemistry and Pharmacy, 2023)

Potential role of dietary Boswellia serrata resin against mancozeb fungicide-induced immune-antioxidant suppression, histopathological alterations, and genotoxicity in Nile tilapia, Oreochromis niloticus - Afaf N. Abdel Rahman; Dalia E. Altohamy; Gehad E. Elshopakey; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nora M. Elseddawy; Aya Elgamal; Shefaa M. Bazeed; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquatic Toxicology, 2023)

Fabrication and optimization of itraconazole-loaded zein-based nanoparticles in coated capsules as a promising colon-targeting approach pursuing opportunistic fungal infections - Shery Adel; Rania H. Fahmy; Ibrahim Elsayed; Magdy I. Mohamed; Reem R. Ibrahim (Drug Delivery and Translational Research, 2023)
Itraconazole (ITZ), a broad-spectrum antifungal drug, was formulated into colon-targeting system aiming to treat opportunistic colonic fungal infections that commonly infect chronic inflammatory bowel diseases (IBD) patients due to immunosuppressive therapy. Antisolvent precipitation technique was employed to formulate ITZ-loaded zein nanoparticles (ITZ-ZNPs) using various zein: drug and aqueous:organic phase ratios. Central composite face-centered design (CCFD) was used for statistical analysis and optimization. The optimized formulation was composed of 5.5:1 zein:drug ratio and 9.5:1 aqueous:organic phase ratio with its observed particle size, polydispersity index, zeta potential, and entrapment efficiency of 208 ± 4.29 nm, 0.35 ± 0.04, 35.7 ± 1.65 mV, and 66.78 ± 3.89%, respectively. ITZ-ZNPs were imaged by TEM that revealed spherical core–shell structure, and DSC proved ITZ transformation from crystalline to amorphous form. FT-IR showed coupling of zein NH group with ITZ carbonyl group without affecting ITZ antifungal activity as confirmed by antifungal activity test that showed enhanced activity of ITZ-ZNPs over the pure drug. Histopathological examination and cytotoxicity tests ensured biosafety and tolerance of ITZ-ZNPs to the colon tissue. The optimized formulation was then loaded into Eudragit S100-coated capsules and both in vitro release and in vivo X-ray imaging confirmed the success of such coated capsules in protecting ITZ from the release in stomach and intestine while targeting ITZ to the colon. The study proved that ITZ-ZNPs is promising and safe nanoparticulate system that can protect ITZ throughout the GIT and targeting its release to the colon with effectual focused local action for the treatment of colon fungal infections. Graphical Abstract

Kidney bean protein hydrolysate as a fish meal replacer: Effects on growth, digestive enzymes, metabolic functions, immune-antioxidant parameters and their related gene expression, intestinal and muscular gene expression - Rowida E. Ibrahim; Samar A. Tolba; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Shimaa I. Shalaby; Ali Osman; Tarek Khamis; Mohamed A. Eissa; Simon J. Davies; Shimaa A. Amer (Aquaculture, 2023)

Development and validation of a risk prediction nomogram for serious arrhythmias in acute digoxin toxicity among pediatrics: A multicenter study - Dina El Gameel; Asmaa Fady Sharif; Osama Shoeib; Elsayed Ibrahim Elgebally; Manar Maher Fayed (Toxicon, 2023)

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Acute mancozeb-fungicide exposure induces neuro-ethology disruption, health disorders, and immune-oxidative dysfunction in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Mohamed A. Elbealy; Gamal A. Salem; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Ahmed Asaid Elkady; Simon J. Davies; Afaf N. Abdel Rahman (Aquatic Toxicology, 2023)

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Resveratrol and Dulaglutide ameliorate adiposity and liver dysfunction in rats with diet-induced metabolic syndrome: Role of SIRT-1 / adipokines / PPARγ and IGF-1 - Hanan Abdel Moneam A. Shamardl; Noha A. Ibrahim; Dina H. Merzeban; Azza M. Elamir; Rehab M. Golam; Asmaa M. Elsayed (DARU Journal of Pharmaceutical Sciences, 2023)
Background Adiposity and non-alcoholic fatty liver disease (NAFLD) are common characteristics of metabolic syndrome (MS). Understanding the underlying pathogenesis is crucial for the development of new remedies. Resveratrol controls obesity and glycemic disorders in patients with MS. Objectives This study aimed to evaluate the effect of resveratrol and dulaglutide on adipose tissues and liver in rats with MS, declaring their possible mechanisms. Methods Rats allocated as Control, MS (induced by a high fat/ high sucrose diet for eight weeks), MS + Resveratrol (30 mg/kg/day orally), and MS + Dulaglutide (0.6 mg/kg twice weekly SC); drugs administration was in the last four weeks. Serum biochemical measurements were done. Liver and visceral fat were processed for biochemistry, histopathology, and immunohistochemistry. Results MS results demonstrated significantly increased systolic and diastolic blood pressure, anthropometric measurements, serum levels of alanine aminotransferase (ALT), glycemic indices, and lipids with decreased HDL-C. Tissue levels of leptin, malondialdehyde (MDA), and TNF-α reactivity significantly increased. Expression of adiponectin, PPARγ, and insulin growth factor-1 (IGF-1) decreased. Also, Western blotting mRNA gene expression of liver SIRT-1 was down-regulated. Resveratrol and dulaglutide significantly and effectively reversed MS complexity, ameliorating all findings, particularly NAFLD and adiposity-induced inflammation. Resveratrol significantly appears superior to dulaglutide regarding the effects on hemodynamics, lipids, adipokines, IGF-1 levels, and adipocyte size. Parallel, dulaglutide has more influence on glycemic control. Conclusion Protective effects of the drugs may be through correlations between SIRT-1/adipokines/IGF-1 and PPARγ, improving the cross-talk between insulin resistance, obesity markers, liver dysfunction, and TNF-α. Promising multi-beneficial therapies of resveratrol or dulaglutide in MS are recommended clinically for this purpose. Graphical Abstract Showing the Experimental Design

Clarithromycin-, and metronidazole-resistant Helicobacter pylori isolated from raw and ready-to-eat meat in Mansoura, Egypt - Aya Elsayed Maghrabia; Hend Ali Elshebrawy; Mahmoud Ahmed Mahros; Mohammed Mohammed Elgazzar; Khalid Ibrahim Sallam (International Journal of Food Microbiology, 2023)

Effects of dietary supplementation of chromium methionine chelate on growth performance, oxidative stress, hematological indices, and carcass traits of broiler chickens - Ibrahim M. I. Youssef; Ibrahim M. I. Abdo; Hassan F. A. Elsukkary; Magdy F. El-Kady; Magdy Elsayed (Tropical Animal Health and Production, 2022)
This study was conducted to evaluate the dietary effects of chromium methionine (Cr-Meth) chelate on growth performance, oxidative stress parameters, blood biochemistry, and carcass traits of broiler chickens. An experiment was conducted on 34,000 1-day-old straight-run broiler chicks (Indian River; 42.0 ± 0.03) at a commercial farm. The chicks were divided randomly into 3 groups; the first group contained 17,000 birds, which used as a control, whereas the second and third groups consisted of 7000 and 10,000 birds, respectively, with 5 replicates per group. A completely randomized design was used. The birds were fed the experimental diets containing graded levels of Cr-Meth chelate: 0 (control), 50, and 100 g/ton. This compound consisted of chromium (0.4%) chelated with methionine, and it supply the diets with 200 and 400 ppb Cr for the used levels of 50 and 100 g/ton feed, respectively. Growth performance indices (body weight, body weight gain, feed intake, and feed conversion ratio) were measured throughout the experiment. At the end of experiment, 10 birds per treatment were slaughtered, and the carcass yield with relative weight of the internal organs was determined. Also, blood samples were taken and analyzed for glutathione peroxidase activity, malondialdehyde, ALT, AST, total protein, albumin, glucose, urea, creatinine, triglycerides, and total cholesterol. It was found that Cr-Meth improved the body weight, weight gain, feed intake, and feed conversion ratio of broilers. Moreover, it reduced the mortality rate of birds. The chelated chromium can alleviate the oxidative status of birds by increasing the plasma glutathione peroxidase activity and reducing the serum malondialdehyde level. It was observed that the effects of 100 g/ton Cr-Meth chelate on performance indices, mortality rate, and oxidative stress parameters were better than that of 50 g/ton inclusion rate. Supplementation of Cr-Meth increased the total protein level, but reduced the glucose, total cholesterol, and triglyceride concentrations in the blood serum. In addition, it increased the carcass yield and reduced the abdominal fat percentage of the birds’ carcass. Therefore, chromium can be included in diets of broilers at a rate of 200 to 400 ppb, and the higher concentration was more effective than the lower one. So, it can be recommended to use Cr-Meth chelate in broiler diets at 100 g/ton to improve the productive performance and reduce the oxidative stress of birds.

Evaluation of Pediatric Early Warning System and Drooling Reluctance Oropharynx Others Leukocytosis scores as prognostic tools for pediatric caustic ingestion: a two-center, cross-sectional study - Asmaa Fady Sharif; Dina El Gameel El Gameel; Sanaa Abd El-Fatah Abdo; Elsayed Ibrahim Elgebally; Manar Maher Fayed (Environmental Science and Pollution Research, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Development of activated carbon fibers for removal of organic contaminants - D. S. S. Alkathiri; M. A. Sabri; T. H. Ibrahim; Y. A. ElSayed; F. Jumean (International Journal of Environmental Science and Technology, 2020)

Response surface optimization of biocompatible elastic nanovesicles loaded with rosuvastatin calcium: enhanced bioavailability and anticancer efficacy - Ibrahim Elsayed; Rania Moataz El-Dahmy; Soad Z. El-Emam; Ahmed Hassen Elshafeey; Nabaweya Abdelaziz Abd El Gawad; Omaima Naim El-Gazayerly (Drug Delivery and Translational Research, 2020)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Study of the gut Microbiome Profile in Children with Autism Spectrum Disorder: a Single Tertiary Hospital Experience - Shwikar AbdelSalam Ahmed; Azza Mahmoud Elhefnawy; Hanan Galal Azouz; Yara Safwat Roshdy; Mona Hamdy Ashry; Ahmed Elsayed Ibrahim; Marwa Ahmed Meheissen (Journal of Molecular Neuroscience, 2020)

Biochemical study on modifying role of variants of leptin gene and its receptor on serum leptin levels in breast cancer - Safaa I. Tayel; Alshimaa M. Alhanafy; Solwan M. Ahmed; Abdelmoneim A. Eltorgoman; Ibrahim E. Elsayed (Molecular Biology Reports, 2020)

A comparative study on the possible protective effect of esomeprazole, spirulina, wheatgrass on indomethacin-induced gastric ulcer in male albino rats - Amy Fakhry Boushra; Asmaa Mohammed Elsayed; Noha Abdellatif Ibrahim; Maha Khaled Abdelwahed; Eman Ibrahim Ahmed (Molecular Biology Reports, 2019)

Identification of serum N-glycoproteins as a biological correlate underlying chronic stress response in mice - Motamed Elsayed Mahmoud; Ibrahim F. Rehan; Kh. El-Dawy Ahmed; Amany Abdelrahman; Saeed Mohammadi; Ahmed F. Abou-Elnaga; Mohammed Youssef; Hassan Mahmoud Diab; Doaa Salman; Asmaa Elnagar; Hesham H Mohammed; Obeid Shanab; et al. (Molecular Biology Reports, 2019)

RETRACTED ARTICLE: Effects of genistein on pentylenetetrazole-induced behavioral and neurochemical deficits in ovariectomized rats - Amr A. Elsayed; Esther T. Menze; Mariane G. Tadros; Bassant M. M. Ibrahim; Nagwa A. Sabri; Amani E. Khalifa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

National collaboration in geo-spatial information: NARSSGeoPortal case study - Rania Elsayed Ibrahim; Amr Elramly (Spatial Information Research, 2017)

Cytotoxic ceramides from the Red Sea sponge Spheciospongia vagabunda - Enas Elsayed Eltamany; Amany K. Ibrahim; Mohamed M. Radwan; Mahmoud A. ElSohly; Hashim A. Hassanean; Safwat A. Ahmed (Medicinal Chemistry Research, 2015)

The geometric configuration of the newly discovered Abu Deleig sedimentary sub-basin, Central Sudan, using remote sensing, structural analysis, and geophysical survey - Abdalla E. M. Elsheikh; Khalid A. Elsayed Zeinelabdein; Sami O. H. El Khidir; Abdalla E. Ibrahim (Arabian Journal of Geosciences, 2014)

Groundwater balance in the Khor Arbaat basin, Red Sea State, eastern Sudan - Abdalla E. M. Elsheikh; Khalid A. Elsayed Zeielabdein; Ibrahim A. A. Babikir (Hydrogeology Journal, 2009)

The changing patterns of bladder cancer in Egypt over the past 26 years - Ashley S. Felix; Amr S. Soliman; Hussein Khaled; Mohamed S. Zaghloul; Mousumi Banerjee; Manal El-Baradie; Mohamed El-Kalawy; Alaa A. Abd-Elsayed; Kadry Ismail; Ahmed Hablas; Ibrahim A. Seifeldin; Mohamed Ramadan; et al. (Cancer Causes & Control, 2008)